2020
DOI: 10.1073/pnas.2006109117
|View full text |Cite
|
Sign up to set email alerts
|

Helper bacteria halt and disarm mushroom pathogens by linearizing structurally diverse cyclolipopeptides

Abstract: The bacterial pathogen Pseudomonas tolaasii severely damages white button mushrooms by secretion of the pore-forming toxin tolaasin, the main virulence factor of brown blotch disease. Yet, fungus-associated helper bacteria of the genus Mycetocola (Mycetocola tolaasinivorans and Mycetocola lacteus) may protect their host by an unknown detoxification mechanism. By a combination of metabolic profiling, imaging mass spectrometry, structure elucidation, and bioassays, we found that the helper bacteria inactivate to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 34 publications
0
14
0
Order By: Relevance
“…Tolaasin, sessilin, and viscosin are well-characterized non-ribosomal peptides with antifungal activity. The tolaasin was first characterized in the fungal pathogen Pseudomonas tolaasii which is the causative agent of the Brown blotch disease, while viscosin and sessilin have been found to be effective against Aspergillus fumigatus , Batrachochytrium dendrobatidis, Rhizoctonia solani, and Pythium myriotylum [ 30 , 31 ].…”
Section: Resultsmentioning
confidence: 99%
“…Tolaasin, sessilin, and viscosin are well-characterized non-ribosomal peptides with antifungal activity. The tolaasin was first characterized in the fungal pathogen Pseudomonas tolaasii which is the causative agent of the Brown blotch disease, while viscosin and sessilin have been found to be effective against Aspergillus fumigatus , Batrachochytrium dendrobatidis, Rhizoctonia solani, and Pythium myriotylum [ 30 , 31 ].…”
Section: Resultsmentioning
confidence: 99%
“…5 ). A recent study also demonstrated that a lipopeptide of a pathogen ( Pseudomonas tolaasii ) is modified by a “helper” bacterium to protect the mushroom Agaricus bisporus from the pathogen’s virulence factors ( 42 ). Furthermore, lipopeptide modifications are commonly used for niche protection—a prominent trait in soil-dwelling Streptomyces strains against a competing Bacillus sp.…”
Section: Resultsmentioning
confidence: 99%
“…Considering the food importance of mushroom species damaged by the above cited Pseudomonas strains and the consequent heavy economic losses, recently some attempts were made to avoid these severe problems. Some positive results were obtained using helper bacteria belonging to the Mycetocola genus which inactivated tolaasin by hydrolyzing the lactone ring and thus generating a liner peptide [ 142 ]. A different mechanism of tolaasin detoxification seemed to be operated by Microbacterium foliorum , which hydrolyzed the peptide chain in two points [ 143 ].…”
Section: Lipodepsipeptides Produced By Bacteria Pathogens Of Mushroomsmentioning
confidence: 99%